2022
DOI: 10.3389/fimmu.2022.864671
|View full text |Cite
|
Sign up to set email alerts
|

Antigen and Cell-Based Assays for the Detection of Non-HLA Antibodies

Abstract: To date, human leukocyte antigens (HLA) have been the major focus in the approach to acute and chronic antibody-mediated rejection (AMBR) in solid-organ transplantation. However, evidence from the clinic and published studies has shown that non-HLA antibodies, particularly anti-endothelial cell antibodies (AECAs), are found either in the context of AMBR or synergistically in the presence of donor-specific anti-HLA antibodies (DSA). Numerous studies have explored the influence of AECAs on clinical outcomes, yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Furthermore, while antibodies against recipient grafts are commonly associated with MHC-directed responses, it is important to acknowledge that not all immune responses in transplantation are MHC-mediated. Histocompatibility testing laboratories play a crucial role in the detection of non-MHC antigens, particularly in the context of organ transplantation [49,53,54].…”
Section: Epitope-based Matching Algorithmsmentioning
confidence: 99%
“…Furthermore, while antibodies against recipient grafts are commonly associated with MHC-directed responses, it is important to acknowledge that not all immune responses in transplantation are MHC-mediated. Histocompatibility testing laboratories play a crucial role in the detection of non-MHC antigens, particularly in the context of organ transplantation [49,53,54].…”
Section: Epitope-based Matching Algorithmsmentioning
confidence: 99%
“…The pretransplant determination of HLA mismatches between recipients and donors is known for a long time in order to reduce allograft rejections. In addition, several non-HLA antibodies have been reported to cause rejection and allograft nephropathy ( 47 51 ). In their retrospective investigation, Lamarthée et al.…”
Section: Pretransplant Biomarkers and Posttransplant Rejectionmentioning
confidence: 99%
“…reported that higher levels of non-HLA antibodies directed against endothelial cells predicted antibody-mediated rejection histology ( 50 ). Several assays have been described to detect non-HLA antibodies ( 51 ). The importance of the genetic mismatch of non-HLA haplotypes for transplant outcome had been investigated by Reindl-Schwaighofer et al.…”
Section: Pretransplant Biomarkers and Posttransplant Rejectionmentioning
confidence: 99%
“…C4d negative, DSA negative, biopsies with interstitial inflammation, tubulitis, and MVI are being increasingly recognized [2]. This phenomenon is most often attributed to non-HLA antibody or NK cell mediated tissue injury, and this may be true in some cases [3][4][5][6]. However, in our experience, these biopsies often contain abundant T-cell infiltrates and readily demonstrable tubulitis, yet the possibility that these can primarily reflect T-cell mediated rejection (TCMR) is not often considered [7].…”
Section: Introductionmentioning
confidence: 99%